PENGUKURAN POSTUR LANSIA YANG MENGALAMI KIFOSIS, LORDOSIS DAN SKOLIOSIS DI DESA BINAAN FISIOTERAPI - Nurseptiani, Dzikra; Lia Dwi Prafitri; Muhammad Daffa’ Al Ghifary Caesario Putra (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the efforts needed in solving the problems of the elderly is with promotive, preventive, curative, and rehabilitative. One of these services can be provided in certain communities such as built villages that have been managed by Physiotherapy Bachelor Study Program of Faculty of Health Sciences Universitas Muhammadiyah Pekaangan Pekalongan. The role of the physiotherapist here is related to the changes in posture experienced by the elderly that are the impact of changes in the musculoskeletal system. One of the changes is the posture of the elderly who have begun to bend or so-called kyphosis which can be detected by examining the position of the flexion of the trunk. Other changes in the shape of the posture in the elderly are lordosis and scoliosis. Lordosis is a spinal disorder of the lumbar region that has excessive curvature, the bone curves back so excessively that it seems as if the bone is pulled forward.. When viewed from the left side of the patient, the lower back forms the letter “C”. As for posture changes scoliosis is a condition of vertebral deformity with a characteristic lateral deviation of at least 10° with rotation of the vertebrae. This scloliosis can be seen when the structure of the spine is shaped like the letter “S”. Some of the problems faced by partners are the need for maintenance with the form of approach activities carried out directly with simple methods of extension, observation and posture examination where later the elderly will be given education about daily activities so as not to aggravate the situation of their posture. From this effort, it was found that as many as 24 elderly experienced a change in posture towards kyphosis, 4 elderly people had lordosis posture and 2 scoliosis. Keywords: Elderly; Kiphosis; Lordosis; Scoliosis